Perfluoroarene induces a pentapeptidic hydrotrope into a pH-tolerant hydrogel allowing naked eye sensing of Ca2+ ions. Issue 5 (18th January 2019) - Maiti, Bappa; Bhattacharjee, Subham; Bhattacharya, Santanu
Abstract : Bilayer organization of the 1 : 1 PyP : OFN gel and reinforcement of the native gel after addition of Ca 2+ ions. Abstract : Self-assembly of a novel thermoresponsive, pyrene-appended oligopeptide sequence VPGKP (PyP) leads to the formation of spherical aggregates in water. The sizes of the globular aggregates of the peptide, PyP, strongly depend on the temperature of its suspension in water and decrease with the decrease in temperature showing a lower critical solution temperature (LCST) phenomenon. Furthermore, a pyrene–octafluoronaphthalene (OFN) 'pair' has been used as a supramolecular synthon to induce hydrogelation of PyP in the presence of an equimolar amount of OFN via complementary quadrupole–quadrupole interactions. The gel shows excellent pH tolerance and thixotropic behavior. Detailed studies suggest the existence of lamellar packing of the gelators in a right-handed helical fashion which yields globular aggregates. The globular aggregates are sticky in nature and form a gel via inter-globular interactions. Addition of Ca 2+ ions reinforces the mechanical strength and also reduces the critical gelator concentration of the native gel through coordination with the free –COO − group of the gelator. Therefore, the present hydrogel system could further be used as a naked eye sensor of Ca 2+ ions.